2013
DOI: 10.1007/s10867-013-9321-0
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical electrical conductivity of hydrogen-bonded benzamide-derived molecules and single DNA bases

Abstract: A benzamide molecule is used as a "reader" molecule to form hydrogen bonds with five single DNA bases, i.e., four normal single DNA bases A,T,C,G and one for 5methylC. The whole molecule is then attached to the gold surface so that a meta-molecule junction is formed. We calculate the transmission function and conductance for the five metal-molecule systems, with the implementation of density functional theory-based nonequilibrium Green function method. Our results show that each DNA base exhibits a unique cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 32 publications
0
4
1
Order By: Relevance
“…7,33 The results showed that the electronic density ρ ( r ) of the C–H 1 ⋯O interaction in DPP-R (0.01911) is greater than that of DPP-B (0.01754), indicating a stronger C–H 1 ⋯O interaction in DPP-R, which favors the charge transfer efficiency. 9 This inference contradicts our experimental results, conversely demonstrating that the larger single-molecule conductance of DPP-B may be attributed to its unique S⋯π interactions which are absent in DPP-R.…”
contrasting
confidence: 93%
See 1 more Smart Citation
“…7,33 The results showed that the electronic density ρ ( r ) of the C–H 1 ⋯O interaction in DPP-R (0.01911) is greater than that of DPP-B (0.01754), indicating a stronger C–H 1 ⋯O interaction in DPP-R, which favors the charge transfer efficiency. 9 This inference contradicts our experimental results, conversely demonstrating that the larger single-molecule conductance of DPP-B may be attributed to its unique S⋯π interactions which are absent in DPP-R.…”
contrasting
confidence: 93%
“…Single-molecule conductance measurement (SMCM) techniques have found widespread application in studying various intra-/inter-molecular non-covalent interactions including hydrogen bonding, pÁ Á Áp stacking, and SÁ Á ÁF/O interactions. [9][10][11][12] Therefore, this advancement paves the way to gain a thorough understanding of the impact of SÁ Á Áp interactions on charge transport.…”
mentioning
confidence: 99%
“…The later result may lead to the conclusion that the contribution of conductivities from the cations to be very small. This could be a consequence of their small charge density, large molar mass, large surface area, as well as the presence of coordinated water, which forms hydrogen bonding with solvent water cavity surrounding the cation that increases the drifting (counter directional) speed (Chen, 2013). Hence, the speed of mobility of the cation decreases as a result of the decrease in the kinetic energy imparted by the electric field from measurement instrument (Atkins & Trapp, 1994).…”
Section: Molar Conductance Of the Metal Complexesmentioning
confidence: 99%
“…21 The electrical conductivity between benzamide-derived molecules and single DNA bases was shown to be highly sensitive to the change in hydrogen bond length. 22 These previous works inspired us to explore the role of hydrogen bonds in thermal and electrical transport in 2D graphamid.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Hydrogen bond dynamics in a hydrogen-bonded organic conductor crystal was leveraged to enable an electrical conductivity and magnetism switch . The electrical conductivity between benzamide-derived molecules and single DNA bases was shown to be highly sensitive to the change in hydrogen bond length . These previous works inspired us to explore the role of hydrogen bonds in thermal and electrical transport in 2D graphamid.…”
Section: Introductionmentioning
confidence: 99%